HISTORICAL TOURISM MANAGEMENT THA RUEA DISTRICT, PHRA NAKHON SI AYUTTHAYA PROVINCE: THE 117TH YEAR VISIT UNOFFICIALLY OF THE NAKORN NOI OF KING RAMA V. - Yansombat, Narumol; Chantanee , Metharat (Journal of MCU Social Science Review, 2023)
This research aims 1. To study the potential of historical tourist attractions on a visit to the beginning of Nakhon Noi; Tha Ruea District, Phra Nakhon Si Ayutthaya Province 2. To present a guideline for managing historical tourism on a visit to Nakhon Noi; Thrue District, Phra Nakhon Si Ayutthaya Province. 3. To create tourism activities for the community to support historical attractions. The research methods consist of the qualitative. The sample group consisted of 45 people, consisting of local historians, the custodian of the ancient site where he had visited or related persons, academicians and tourists. Data were collected by observation. in-depth interview and focus group discussion using a target group of 15 people. Data were analyzed using content analysis and descriptive writing. The results of the research were as follows: 1. Tha Ruea District has potential in terms of historical tourism as follows: tourist attraction, tourist support and management 2. There are 5 management guidelines for historical tourism management of the visit to Nakhon Noi; Tha Ruea District Phra Nakhon Si Ayutthaya Province as follows: resources, stakeholder participation, customers or tourists, tourism activities in the area and impacts from tourism. 3. Create tourism activities for the community to support tourist attractions by designing a tourist route tourism program. Make a tourist map and create social media through online channels.